Evaluation of an in-work tax credit reform in Sweden: effects on labor supply and welfare participation of single mothers - Rolf Aaberge; Lennart Flood (Institute for the Study of Labor (IZA), 2008)
The purpose of this paper is to evaluate a recent Swedish in-work tax credit reform where we pay particular attention to labor market exclusion; i.e. individuals in as well as outside the labor force are included in the analysis. To highlight the importance of the joint effects from the tax and the benefit systems it appears particular relevant to analyze the labor supply behavior of single mothers. To this end, we estimate a structural microeconometric model of labor supply and welfare participation. The model accounts for heterogeneity in consumption-leisure preferences as well as for constraints in job opportunities. The results of the evaluation show that the reform generates welfare-gains for virtually every single mother, and moreover benefits low-income households. Finally, due to increased labor supply and decline in welfare participation we find that this reform is almost self-financing.
urn:nbn:de:101:1-2008101519
Keywords: J22; 330; Labor supply; single mothers; in-work tax credit; social assistance; random utility model; Steuerbegünstigung; Alleinerziehende; Arbeitsangebot; Sozialhilfe; Wirkungsanalyse; Schweden